Impaired Neuronal Nitric Oxide Synthase–Mediated Vasodilator Responses to Mental Stress in Essential Hypertension. Issue 4 (April 2015) - Khan, Sitara G.; Geer, Amber; Fok, Henry W.; Shabeeh, Husain; Brett, Sally E.; Shah, Ajay M.; Chowienczyk, Philip J.
<x xml:space="preserve">Abstract</x> Neuronal NO synthase (nNOS) regulates blood flow in resistance vasculature at rest and during mental stress. To investigate whether nNOS signaling is dysfunctional in essential hypertension, forearm blood flow responses to mental stress were examined in 88 subjects: 48 with essential hypertension (42±14 years; blood pressure, 141±17/85±15 mm Hg; mean±SD) and 40 normotensive controls (38±14 years; 117±13/74±9 mm Hg). A subsample of 34 subjects (17 hypertensive) participated in a single blind 2-phase crossover study, in which placebo or sildenafil 50 mg PO was administered before an intrabrachial artery infusion of the selective nNOS inhibitor S-methyl-L-thiocitrulline (SMTC, 0.05, 0.1, and 0.2 μmol/min) at rest and during mental stress. In a further subsample (n=21) with an impaired blood flow response to mental stress, responses were measured in the presence and absence of the α-adrenergic antagonist phentolamine. The blood flow response to mental stress was impaired in hypertensive compared with normotensive subjects (37±7% versus 70±8% increase over baseline; P<0.001). SMTC blunted responses to mental stress in normotensive but not in hypertensive subjects (reduction of 40±11% versus 3.0±14%, respectively, P=0.01, between groups). Sildenafil reduced the blood flow response to stress in normotensive subjects from 89±14% to 43±14% (P<0.03) but had no significant effect in hypertensive subjects. Phentolamine augmented impaired blood flow responses to mental stress from 39±8% to 67±13% (P<0.02). Essential hypertension is associated with impaired mental stress–induced nNOS-mediated vasodilator responses; this may relate to increased sympathetic outflow in hypertension. nNOS dysfunction may impair vascular homeostasis in essential hypertension and contribute to stress-induced cardiovascular events.